Adoção embrionária - Nascimento, Alexandre Lescura do (2011)
Assisted human reproductive techniques have the objective to aid individuals with fertility difficulties. As a rule, several embryos are created when female gametes are fertilized in vitro. However, not all of such embryos are fit to be used in the same embryonic introduction procedure into the uterus. The surplus of such human embryos, better known as exceeding embryos, once in cryopreservation, experiment development suspension for undetermined period of time. As per Law 11.105/05 (Biosafety Law), all genitors of frozen embryos up to the date of its publication, even if such embryos are deemed unfeasible, as well as all genitors of frozen embryos at any other time, provided such embryos are also deemed unfeasible, have the faculty to offer such embryos to be used in stem cell research and for therapeutic procedures. Embryonic Adoption then appears as an option to such legal faculty or as a sole alternative to be exercised by the genitors of such exceeding embryos who are not entitled to that faculty, but are willing to allow such embryos to be born. In this new mode of adoption, embryos that are no longer part of their genitors parenting plans may be taken by other persons willing to provide them with conditions for gestation, birth, family and dignity